2021
DOI: 10.3389/fnut.2021.725529
|View full text |Cite
|
Sign up to set email alerts
|

Millets Can Have a Major Impact on Improving Iron Status, Hemoglobin Level, and in Reducing Iron Deficiency Anemia–A Systematic Review and Meta-Analysis

Abstract: The prevalence of iron deficiency anemia is highest among low and middle-income countries. Millets, including sorghum, are a traditional staple in many of these countries and are known to be rich in iron. However, a wide variation in the iron composition of millets has been reported, which needs to be understood in consonance with its bioavailability and roles in reducing anemia. This systematic review and meta-analysis were carried out to analyze the scientific evidence on the bioavailability of iron in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…The findings of this review paper provide scientific evidence supporting diversification of standard diets for children using millets as a solution to malnutrition. Furthermore, millets are a basket of a wide range of nutrients and have been scientifically shown to contribute to serving many of the significant nutrition and health needs globally [ 12 , 13 , 14 , 15 ], not only by tackling child undernutrition, but also by managing type 2 diabetes [ 12 ], lowering total cholesterol levels, obesity [ 13 ], and iron deficiency anaemia [ 14 ]. To bring this solution to reality, awareness about the nutritional value is needed to drive demand and investments in millets along the value chain, from fork to farm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this review paper provide scientific evidence supporting diversification of standard diets for children using millets as a solution to malnutrition. Furthermore, millets are a basket of a wide range of nutrients and have been scientifically shown to contribute to serving many of the significant nutrition and health needs globally [ 12 , 13 , 14 , 15 ], not only by tackling child undernutrition, but also by managing type 2 diabetes [ 12 ], lowering total cholesterol levels, obesity [ 13 ], and iron deficiency anaemia [ 14 ]. To bring this solution to reality, awareness about the nutritional value is needed to drive demand and investments in millets along the value chain, from fork to farm.…”
Section: Discussionmentioning
confidence: 99%
“…The year 2023 has been approved by the United Nations as the International Year of Millets, which is expected to attract major attention to millets. Previous systematic reviews and meta-analyses conducted on millets’ health and nutritional benefits showed that regular consumption of millets could help manage the risk of developing type 2 diabetes [ 12 ], reduce hyperlipidaemia, hypertension, and body mass index (BMI), thereby helping manage cardiovascular disease risk [ 13 ], improve haemoglobin level, and reduce anaemia [ 14 ], as well as helping calcium retention [ 15 ]. However, scientific evidence of millets’ role in addressing global crises, such as impaired growth, has had fewer studies undertaken in order to prioritize these crops in nutritional interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Data in food composition tables often are limited because they include analysis of food available in markets and do not consider local crop varieties that vary in their nutrition content due to individual characteristics, climate, soil, etc. For instance, a recent study analyzing the nutrition content of millets showed that some varieties could have three times more iron than others ( 43 ). Therefore, using these varieties could be strategic to reduce iron deficiency anemia with low-cost potential.…”
Section: Discussionmentioning
confidence: 99%
“…The decline in the cultivation and consumption of traditional coarse cereals with high iron content led to a decline in dietary iron content in the Indian diet, which coincides with an increased incidence of IDA in women and children [ 96 ]. In recent interventions, increased consumption of coarse cereals, particularly millets, reduced the prevalence of IDA in Indian women and children [ 97 ]. The recent meta-analysis of 22 studies has shown that regular consumption of millets effectively increased Hb levels by 13.2% and serum ferritin by 54.7% [ 97 ].…”
Section: Efficacy Of Ida Prevention Programs In Indiamentioning
confidence: 99%